The CdS/CdSe/ZnS Photoanode Cosensitized Solar Cells Basedon Pt, CuS, Cu2S, and PbS Counter Electrodes. (27th February 2014) - Ha Thanh, Tung; Huynh Thanh, Dat; Quang Lam, Vinh
Abstract : Highly ordered mesoporous TiO2 modified by CdS, CdSe, and ZnS quantum dots (QDs) was fabricated by successive ionic layer adsorption and reaction (SILAR) method. The quantity of material deposition seems to be affected not only by the employed deposition method but also and mainly by the nature of the underlying layer. The CdS, CdSe, and ZnS QDs modification expands the photoresponse range of mesoporous TiO2 from ultraviolet region to visible range, as confirmed by UV-Vis spectrum. Optimized anode electrodes led to solar cells producing high current densities. Pt, CuS, PbS, and Cu2 S have been used as electrocatalysts on counter electrodes. The maximum solar conversion efficiency reached in this work was 1.52% and was obtained by using Pt electrocatalyst. CuS, PbS, and Cu2 S gave high currents and this was in line with the low charge transfer resistances recorded in their case.